Age of children contributes to potential drug interaction at nine primary health cares - Sari, Flori R. (The Avicenna Medical Journal, 2023)
Introduction: Adverse drug reaction including drug interaction should be prevented early in children’s patients since children are vulnerable subjects due to their biological development process. Our study aimed to identify the potential drug interaction in children’s patients from nine primary health cares (PHC) at Tangerang.Methods: This study was done with an analytical cross-sectional approach at nine PHC. All children patients from age 1 to 18 years old were recruited for two weeks study. All prescriptions were analyzed and categorized for potential drug interactions.Results: We identified 19 mild and moderate but not serious potential drug interactions from 791 prescriptions (2%). The most common mild potential drug interaction is paracetamol and domperidone as well as mefenamic acid and dexamethasone for moderate potential drug interaction. Number of drugs and gender did not significantly correlate to potential drug interactions, but age did (p=0.04).Discussion: We identified that age correlated significantly to potential drug interactions. In brief, the older the patients, the higher the possibility for the drug interactions, thus physicians should be more aware in prescribing drugs to older children’s patients.